2016
DOI: 10.1002/mrm.26100
|View full text |Cite
|
Sign up to set email alerts
|

Downfield‐NOE‐suppressed amide‐CEST‐MRI at 7 Tesla provides a unique contrast in human glioblastoma

Abstract: Purpose: The chemical exchange saturation transfer (CEST) effect observed in brain tissue in vivo at the frequency offset 3.5 ppm downfield of water was assigned to amide protons of the protein backbone. Obeying a base-catalyzed exchange process such an amide-CEST effect would correlate with intracellular pH and protein concentration, correlations that are highly interesting for cancer diagnosis. However, recent experiments suggested that, besides the known aliphatic relayednuclear Overhauser effect (rNOE) upf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
184
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(198 citation statements)
references
References 59 publications
12
184
1
1
Order By: Relevance
“…Therefore, the absolute MTR asym (3.5ppm) signal intensity as well as the contrast of the ischemic stroke is reduced by the upfield NOE signals and the use of the asymmetry metric reduces the sensitivity of APT signals in ischemic stroke imaging. It should be mentioned that, contrary to our findings and the basic evidence from studies on cells and tissue (53) and high resolution NMR studies of proteins (56, 57), others have not found a change of relayed-NOE signals following acute stroke (29, 58, 59). The most likely explanation of this is a difference in saturation power B 1 , leading to very different contributions of fast and slow exchanging protons to the Z-spectrum (60).…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, the absolute MTR asym (3.5ppm) signal intensity as well as the contrast of the ischemic stroke is reduced by the upfield NOE signals and the use of the asymmetry metric reduces the sensitivity of APT signals in ischemic stroke imaging. It should be mentioned that, contrary to our findings and the basic evidence from studies on cells and tissue (53) and high resolution NMR studies of proteins (56, 57), others have not found a change of relayed-NOE signals following acute stroke (29, 58, 59). The most likely explanation of this is a difference in saturation power B 1 , leading to very different contributions of fast and slow exchanging protons to the Z-spectrum (60).…”
Section: Discussioncontrasting
confidence: 99%
“…Besides the guanidyl protons, there are other possible contributions to the endogenous CEST signal at 2.0 ppm, such as from the aromatic NOE from mobile proteins as suggested by our group and others (Jin and Kim, 2013; Zaiss et al, 2017), and amide of glutamine (Mori et al, 1998). Since NOE effects are insensitive to pH {Jin, 2013 #2715}, and amide has opposite pH-contrast with guanidyl with our selection of saturation powers, we expect that the pH-contrast at 2.0 ppm should be mostly from the guanidyl protons.…”
Section: Discussionmentioning
confidence: 85%
“…Some authors implied or demonstrated that the background MT asymmetry or NOE effects are negligible at 3T, while others argue that MT asymmetry is more significant than the APT effect even at 3T . According to the recent researches with ultrahigh‐field MRI, NOE imaging has the potential to delineate portions with high cellularity, or BBB disruption in glioma, without contrast agents . MT contrast in the brain tumor has been reported to be decreased compared with white matter, and correlate with nuclear density .…”
Section: Discussionmentioning
confidence: 99%